Solving reading problems across the curriculum - Nicholson, Tom. (Wellington [N.Z.] : Melbourne: New Zealand Council for Educational Research ; Australian Council for Educational Research, 1997)
This book is divided into three parts: Problems; Explanations; and Techniques about solving reading problems.
Keywords: Education; Linguistic teaching; Reading comprehension; Remedical teaching; Reading -- Remedial teaching; Reading comprehension -- Study and teaching